STATE MANAGEMENT OF TOURISM SERVICES IN HA GIANG PROVINCE - Dang Thuy Trang, Le Bach Giang, Pham Minh Dat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tourism is currently an economic spearhead for Vietnam, thereby contributing to promoting sustainable development for the economy of each region, especially for the economy of the northern mountainous locality possibly Ha Giang province. Through this study, the author wants to evaluate the influence of these factors on the state management of tourism services in Ha Giang province. This assessment is done mainly by surveying businesses operating in tourism services in the province with the support of data analysis by specialized software. Through the research, the author wants to show the impact of the factors so that there are effective solutions to promote the development of tourism services in Ha Giang province, Vietnam.